Non-aqueous hybrid supercapacitors fabricated with mesoporous TiO 2 microspheres and activated carbon electrodes with superior performance - Cai, Y.; Zhao, B.; Wang, J.; Shao, Zongping (2014)
Mesoporous TiO2 microspheres, synthesized by a facile template-free solvothermal method and subsequent heat treatment, are exploited as the electrode for hybrid supercapacitors. The effects of the calcination temperature on the phase composition, particulate microstructure and morphology are characterized by XRD, Raman, FE-SEM and N2 adsorption/desorption measurements. Hybrid supercapacitors utilizing the as-prepared TiO2 mesoporous microspheres as the negative electrode and activated carbon (AC) as the positive electrode in a non-aqueous electrolyte are fabricated. The electrochemical performance of these hybrid supercapacitors is studied by galvanostatic charge-discharge and cyclic voltammetry (CV). The hybrid supercapacitor built from TiO2 microspheres calcined at 400 C shows the best performance, delivering an energy density of 79.3 Wh kg-1 at a power density of 178.1 W kg-1. Even at a power density of 9.45 kW kg-1, an energy density of 31.5 Wh kg-1 is reached. These values are much higher than the AC-AC symmetric supercapacitor. In addition, the hybrid supercapacitor exhibits excellent cycling performance, retaining 98% of the initial energy density after 1000 cycles. Such outstanding electrochemical performance of the hybrid supercapacitor is attributed to the matched reaction kinetics between the two electrodes with different energy storage mechanisms.